Analysis of transient electromagnetic fields in electromagnetic rail launcher using an adaptive recursive algorithm - Zhang, Yu-ting; Wang, Zhen-chun (Journal of magnetism and magnetic materials, 2025)
•A dynamic electromagnetic field model for the H-shaped armature, considering geometry and skin effect.•An adaptive recursive algorithm is developed to improve computational efficiency and accuracy.•The method achieves an armature muzzle velocity error below 2.28%, demonstrating high precision.•Experimental validation demonstrates the effectiveness and reliability of the model and solution method. Modeling the electromagnetic rail launch is a critical aspect that provides solid theoretical support for the design and optimization of launch systems. This paper comprehensively considers factors such as armature shape, rail shape, and the skin effect of current to establish a dynamic electromagnetic field model for an H-shaped armature in electromagnetic rail launch. To achieve efficient solutions, an adaptive recursive numerical analysis method is proposed. This method recursively segments the integration intervals of various variables and employs adaptive Simpson’s numerical integration for regression once the integration nodes are determined. This successfully enables the rapid resolution of the dynamic electromagnetic field model, yielding a time-varying inductance gradient. Subsequently, the Runge-Kutta method is used to calculate the velocity and displacement curves of the armature. Experimental validation of the model indicates a 2.28% error in the calculated muzzle velocity of the armature and a maximum error of 4.48% during the launch process. These results strongly validate the proposed model and the adaptive recursive numerical analysis method, providing strong evidence for theoretical analysis in electromagnetic launch technology.